Reversing Nigeria’s food import dependency - agricultural transformation (2017)
Nigeria currently imports foods for domestic consumption of her citizens. This is puzzling because a greater percentage of her population is engaged in agriculture. This is despite the apparent neglect of agriculture since crude oil was discovered in commercial quantities in the early 1970s. Before the discovery of oil in exportable quantities, the country depended largely for her foreign exchange earnings on agricultural exports and the various regions in the country were quite active in agricultural production. The Northern region was noted for the groundnut pyramids that dotted the various parts of the region; the Western region for cocoa and the Eastern region were renowned for palm plantations. This success story was not sustained with the discovery of oil, as agriculture was abandoned and neglected by successive governments in the country. However, the decline in crude oil revenue since 2014 has once again exposed the vulnerability of Nigeria‟s dependence on crude oil as a major earner of foreign exchange. Consequently, Nigeria is finding it difficult to pay for its food import bills and there is hunger in the land. Using exploratory technique with anecdotal evidence, this study highlighted the dangers of relegating agriculture in Nigeria and placed analytical spotlight on agricultural transformation as a solution for reversing the country‟s food import dependency.